Do poles really "save the legs" during uphill pole walking at different intensities? - Giovanelli, N.; Pellegrini, B.; Bortolan, L.; Mari, L.; Schena, F.; Lazzer, S. (European Journal of Applied Physiology, 2023)
Purpose In sky- and trail-running competitions, many athletes use poles. The aims of this study were to investigate whether the use of poles affects the force exerted on the ground at the feet (Ffoot), cardiorespiratory variables and maximal performance during uphill walking.